Comparative Study of Four Layer Vs Short Stretch Bandage for Venous Leg Ulcer Healing - Dr Arun Kumar R; Dr J Sharath Kumar (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Venous leg ulcers (VLUs) are a significant cause of morbidity worldwide. Compression therapy is the cornerstone of treatment, with Four-Layer Bandage (FLB) and Short Stretch Bandage (SSB) being the two most commonly used modalities. This study aims to compare the efficacy of FLB versus SSB in terms of ulcer healing rates. Methods: A prospective, randomized comparative study was conducted in a tertiary care hospital. Thirty-five patients with chronic venous leg ulcers were recruited and randomly assigned to receive either FLB or SSB. Patients were followed for 12 weeks with ulcer size, pain score, and quality of life (QoL) assessed at baseline and at regular intervals. Results: The mean ulcer size reduction was significantly greater in the FLB group compared to the SSB group at 12 weeks (p<0.05). Pain scores improved significantly in both groups, but patients in the FLB group reported better QoL. The rate of complete healing was higher in the FLB group (60%) compared to the SSB group (40%). Conclusion: FLB demonstrated superior healing outcomes compared to SSB in the treatment of VLUs. Further large-scale studies are recommended.